Serum Anti-Müllerian Hormone Levels in Patients with Epithelial Ovarian Cancer. (28th July 2013) - Walentowicz, Pawel; Sadlecki, Pawel; Krintus, Magdalena; Sypniewska, Grazyna; Mankowska-Cyl, Aneta; Grabiec, Marek; Walentowicz-Sadlecka, Malgorzata
Abstract : Objectives . The aim of our study was to examine serum anti-Müllerian hormone (AMH) concentration in ovarian cancer patients in relation to clinicopathological features, such as a pathological subtype of the tumor, (FIGO) stage, grading, and overall 5-year survival. Material and Methods . We enrolled 72 epithelial ovarian cancer patients in our study, aged 45–79 years, who underwent optimal cytoreductive surgery. In all patients, serum AMH concentration was measured using a two-step sandwich type enzyme immunoassay before surgery. As a reference value for women over 45 years we accepted anti-Müllerian hormone concentration below 1 ng/mL. Results . In the whole group of patients with ovarian cancer, median serum concentration of AMH was 0.07 (0.0–0.37) ng/mL, whereas in the group of those with positive AMH values (≥0.14 ng/mL) it was 0.31 (0.15–0.73) ng/mL. No significant correlation was found between serum AMH levels and FIGO stage, histological subtype, or grading (P > 0.05 ). The analysis of five-year survival rate related to AMH levels showed no statistically significant differences. There were no differences in survival rates between patients with positive or negative serum AMH levels. Conclusion. Measurement of serum anti-Müllerian hormone levels was not useful in predicting clinicopathological features and survival in patients with ovarian cancer.